2016
DOI: 10.3233/nre-161329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe spasticity treatment with intrathecal Baclofen in multiple sclerosis patients: Long term follow-up

Abstract: A reduced spasticity and pain was observed after the intrathecal Baclofen infusion for at least 76 months. To obtain these results a dosage adjustment was needed only in the first year after the implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Nine of these studies reported a significant difference in AS/MAS scores between pre-and post-ITB implantation at some point during the follow-up period in each. [6][7][8][9]12,14,15,17,21 Among these 13 studies, 7 reported AS scores, with an average percent reduction from pre-to post-ITB implantation of 61.25%. Four reported MAS scores, with an average percent reduction of 58.23%.…”
Section: Ashworth Scale and Modified Ashworth Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Nine of these studies reported a significant difference in AS/MAS scores between pre-and post-ITB implantation at some point during the follow-up period in each. [6][7][8][9]12,14,15,17,21 Among these 13 studies, 7 reported AS scores, with an average percent reduction from pre-to post-ITB implantation of 61.25%. Four reported MAS scores, with an average percent reduction of 58.23%.…”
Section: Ashworth Scale and Modified Ashworth Scalementioning
confidence: 99%
“…15 Also, Stampacchia et al reported median values for both upper and lower extremities; for the upper extremities, the median and IQR of values showed no change from pre-to postimplantation at two separate time points (12 and 24 months). 21 Thus, in the calculation of percent reduction, the MAS score from 24 months postimplantation (latest time point) was subtracted from the preimplantation MAS score for the lower extremities. 21 Additionally, Sammaraiee et al reported AS for 106 patients from pretrial to 1-year postimplantation.…”
Section: Ashworth Scale and Modified Ashworth Scalementioning
confidence: 99%
See 1 more Smart Citation
“…In the "year" column it can be seen when the paper was published, and in the "number of patients" the amount of people that took participation in the research. In general, the "follow-up" period [14]; [33][34][35][36][37][38][39][40][41]. NS = not specified.…”
Section: Infusion Pumps In Spasticitymentioning
confidence: 99%
“…Intrathecal baclofen (ITB) is administered via a catheter passing into the spinal CSF space and connected to a subcutaneously located pump into the abdomen in a closed system; thus, it is highly effective and lacks the systemic side effects. Chronic and refractory spasticity due to cerebral palsy, multiple sclerosis (MS), spinal cord injuries, traumatic brain injuries, and stroke are among the established indications for ITB treatment [7-13]. However, data on patients with rare conditions such as ataxia and ITB treatment are limited [14-17].…”
Section: Introductionmentioning
confidence: 99%